A perspective on possible amendments in semiconductors for enhanced photocatalytic hydrogen generation by water splitting. (16th November 2021) - Ishaq, Tehmeena; Yousaf, Maryam; Bhatti, Ijaz Ahmad; Batool, Aisha; Asghar, Muhammad Adeel; Mohsin, Muhammad; Ahmad, Muhammad
Abstract: Photocatalytic hydrogen production using solar irradiation is the best solution for existing energy crisis and ecological issues. Various efforts have been made to design a stable, proficient and visible light driven photocatalyst for hydrogen generation. It has been revealed that numerous factors e.g., surface area, morphology, band structure, charge transference and crystallinity affect the solar to hydrogen conversion ability of photocatalyst. Currently, many modification strategies including anion/cation doping, composite formation and alloy fabrication have been advised for semiconductor catalysts to harvest solar light to maximum extent. Moreover, a progression of novel engineering techniques that introduces dye sensitizers, quantum dots and co-catalysts, seems to enhance the photocatalytic efficiency for hydrogen production. In this perspective, we present a summary of various factors that can enhance the effectiveness of hydrogen generation and outline current advancement of frequently used fabricating strategies that look for greater yield of hydrogen. Lastly, emergence of surface plasmon resonance and significance of photocatalyst recycling for hydrogen generation is discussed. It is expected that this perspective will help researchers in designing an efficient photocatalyst for industrial scale hydrogen production. Highlights: Role of surface plasmon resonance in H2 production is of significant importance. Strategies to enhance semiconductor photocatalytic performance is discussed. Effect of doping and alloy fabrication over water splitting is discussed. Role of surface engineering and defects over water splitting is described.